2022
DOI: 10.1136/bmj-2022-070918
|View full text |Cite|
|
Sign up to set email alerts
|

Development and external validation of a risk prediction model for falls in patients with an indication for antihypertensive treatment: retrospective cohort study

Abstract: Objective To develop and externally validate the STRAtifying Treatments In the multi-morbid Frail elderlY (STRATIFY)-Falls clinical prediction model to identify the risk of hospital admission or death from a fall in patients with an indication for antihypertensive treatment. Design Retrospective cohort study. Setting Primary care data from electronic health records contained within the UK Clinical Practice R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Previous studies have reported good validity in the reporting of fractures, but there remains potential biases for our outcomes . As we captured all-cause traumatic fractures, a proportion may have not related to falls, but we were unable to ascertain whether this was the case.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported good validity in the reporting of fractures, but there remains potential biases for our outcomes . As we captured all-cause traumatic fractures, a proportion may have not related to falls, but we were unable to ascertain whether this was the case.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported good validity in the reporting of fractures, but there remains potential biases for our outcomes. [43][44][45][46] As we captured all-cause traumatic fractures, a proportion may have not related to falls, but we were unable to ascertain whether this was the case. Despite this, our analysis for fractures is likely to be more accurate than for falls because of the multifactorial nature of falls.…”
Section: Limitationsmentioning
confidence: 99%
“…These individuals were more likely to be obese, be from an area of high deprivation, or be prescribed multiple antihypertensive medications, but using the present tool alongside existing CVD prediction tools 4 would provide the most personalised risk estimates. Such tools could also be enhanced by incorporating similar evidence regarding the risk of falls 31 to develop a multidimensional antihypertensive harm tool.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the present study developed and validated a clinical prediction model for admission to hospital or death with AKI, and found most patients with an indication for antihypertensives had a very-low risk of AKI. This model could be used to reassure patients starting or up-titrating antihypertensive treatment, and should be used alongside other prediction models for adverse events related to antihypertensive therapy 31 to allow GPs and patients to better understand the full spectrum of benefits and harms from such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is common place in the context of anticoagulation for patients with atrial fibrillation [ 31 ], where prediction models are used to estimate an individual’s risk of stroke (and likelihood of benefiting from treatment) [ 32 ] and weigh this against their risk of a serious bleed (which may be exacerbated by treatment) [ 33 ]. Such models are now being developed in the context of antihypertensive treatment prescription [ 34 , 35 ], and these are needed to facilitate personalised treatment decisions based on an individual’s risk and personal preferences. It is likely to be some time before these are available in routine clinical practice, so in the meantime, the results from our study offer an important insight as to when one might want to consider intervening to prevent an individual from suffering adverse events from antihypertensive treatment.…”
Section: Discussionmentioning
confidence: 99%